Discovery of Antireicheia in Cameroon with description of four new species and discussion on phylogeny and distribution of endogean Reicheiina (Coleoptera: Carabidae: Scaritinae: Clivinini) - Grebennikov, Vasily V.; Bulirsch, Petr; Magrini, Paolo (Zootaxa, 2009)
The endogean carabid genus Antireicheia Basilewsky, 1951, previously know from the eastern and southern Africa and Madagascar is, for the first time, reported west of the Congo basin. Four new species are described and illustrated: A. demirei sp. nov. (Cameroon: Mt. Oku), A. hintelmanni sp. nov. (Cameroon: Mt. Oku), A. deuvei sp. nov. (Cameroon: Mt. Bamboutos) and A. camerounensis sp. nov. (Cameroon: Bafut, Nguemba forest). A key to Cameroonian Antireicheia species is provided. The composition of the subtribe Reicheiina, its monophyly, world distribution, as well as zoogeographical implications of its discovery in Western Africa, are discussed.